ANALYSIS OF THE RELATIONSHIP BETWEEN DIGITAL MARKETING AND COMPETITIVE ADVANTAGE OF MSMEs IN INDONESIA: AN EMPIRICAL STUDY IN THE CREATIVE SECTOR - Setyawati, Amelia; Sugangga, Amelia; Annisa, Rosalina Nur; Setiyawami, Setiyawami; Ogunjemilua, Emmanuel Makanjuola (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
This study aims to analyze the relationship between digital marketing, entrepreneurial ecosystem, and knowledge management on the competitive advantage of micro, small, and medium enterprises (MSMEs) in the creative sector in Indonesia. This study uses a quantitative approach with a survey method on MSME actors in the creative sector in various regions in Indonesia. The research sample consisted of 180 respondents selected through purposive sampling techniques. The data obtained were analyzed using multiple regression techniques to test the causal relationship between the variables studied. The results of the research data analysis concluded that digital marketing, entrepreneurial ecosystem, and knowledge management have a positive and significant effect on competitive advantage. The conclusion of this study confirms that digital marketing can increase market reach and promotion effectiveness. A strong entrepreneurial ecosystem, characterized by policy support, access to funding, and business networks, contributes to creating sustainable competitiveness for MSMEs. In addition, good knowledge management allows MSMEs to manage information and skills more optimally. These findings provide implications for stakeholders in encouraging digitalization strategies, strengthening the entrepreneurial ecosystem, and knowledge management to strengthen the competitiveness of creative sectors of MSMEs in Indonesia.